Thickness dependence of surface plasmon resonance sensor response for metal ion detection - Jung, Seung-A; Lee, Taek-Seong; Kim, Won Mok; Lee, Kyeong-Seouk; Jeong, Doo Seok; Lee, Wook Seong; Kim, Inho (IOP PUBLISHING LTD, 2013)
Surface plasmon resonance (SPR) sensor is one of the most viable technologies for portable and highly sensitive sensing in clinical and environmental applications. A lot of research on SPR sensors based on plasticized polyvinyl chloride (PVC) sensing layers for detection of various metal ions has been well reported, but a study on their correlation between sensing layer thickness and sensor response has been rarely done. The purpose of this study is to investigate thickness dependence of sensing layers on the response time and the sensitivity of SPR sensors based on plasticized PVC. Calcium ionophore was incorporated in the sensing layers for calcium ion detection. Our experimental results showed that thicker sensing layers exhibited higher sensitivity and wider detection range but longer response time. We discussed metal ion diffusion in plasticized sensing layers by correlating numerical calculations with experimental ones in order to understand temporal response of our SPR sensor. The response time also relied on the flow rate of calcium ion solutions, indicating that metal ion diffusion in bulk media is one of the limiting factors.
Keywords: OPTICAL CHEMICAL SENSOR; SELECTIVE ELECTRODES; FILM